A Proactive Approach for Managing COVID-19: The Importance of Understanding the Motivational Roots of Vaccination Hesitancy for SARS-CoV2 - Taylor, Steven; Landry, Caeleigh A.; Paluszek, Michelle M.; Groenewoud, Rosalind; Rachor, Geoffrey S.; Asmundson, Gordon J. G. (Frontiers in Psychology, 2020)
Importance: Vaccination hesitancy—the reluctance or refusal to be vaccinated—is a leading global health threat (WHO, 2019). It is imperative to identify the prevalence of vaccination hesitancy for SARS-CoV2 in order to understand the scope of the problem and to identify its motivational roots in order to proactively prepare to address the problem when a vaccine eventually becomes available. Objective: To identify (1) the prevalence of vaccination hesitancy for a SARS-CoV2 vaccine, (2) the motivational roots of this hesitancy, and (3) the most promising incentives for improving the likelihood of vaccination uptake when a vaccine does become available. Design, Setting, and Participants: A cross-sectional population representative sample of 3,674 American and Canadian adults assessed during the COVID-19 pandemic in May 2020. Main Outcomes: Measures of vaccination intention (i.e., “If a vaccine for COVID-19 was available, would you get vaccinated?”), attitudes toward vaccines in general and specific to SARS-CoV2 using the Vaccination Attitudes Examination Scale, and incentives for getting vaccinated for those who reported they would not get vaccinated. Results: Many American (25%) and Canadian (20%) respondents said that they would not get vaccinated against SARS-CoV2 if a vaccine was available. Nonadherence rates of this magnitude would make it difficult or impossible to achieve herd immunity. Vaccine rejection was most strongly correlated with mistrust of vaccine benefit, and also correlated with worry about unforeseen future effects, concerns about commercial profiteering from pharmaceutical companies, and preferences for natural immunity. When asked about incentives for getting vaccinated, respondents were most likely to report that evidence for rigorous testing and safety of the vaccine were of greatest importance. Conclusions and Relevance: Vaccination hesitancy is a major looming problem for COVID-19. To improve vaccine uptake, it is imperative that the vaccine is demonstrated to the public to be rigorously tested and not perceived as rushed or premature in its dissemination.